Advanced Guidance and Control of Flight Vehicle: Theory and Application (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The application of advanced guidance and control to missiles, hypersonic vehicles, and unmanned aerial vehicles has long represented a research hotspot in academia, and the development of more advanced and intelligent guidance and control technology for flight vehicles has become a focus of research in recent years. In this reprint, studies on the mathematical theory and application of flight vehicle guidance and control are presented. This includes trajectory optimization, online planning, advanced intermediate guidance theoretical methods, terminal guidance theoretical methods, intercept guidance and pursuit and escape guidance, and other topics.